Model-independent PD-SMC method with payload swing suppression for 3D overhead crane systems. (15th August 2019) - Zhang, Menghua; Zhang, Yongfeng; Chen, He; Cheng, Xingong
Highlights: It doesn't need linearization to the dynamics. It is model free. It has a simple structure. Abstract: A model-independent control method, called proportional-derivative with sliding mode control method or PD-SMC in short, is designed for 3D overhead crane systems, where external disturbances, unmodeled and parametric uncertainties are present, to achieve simultaneous trolley positioning and payload swing suppression. One great benefit of the designed controller is its model-independent feature that can avoid requiring exact model knowledge. The proposed control method has the advantages of both simple structure of the PD control method and strong robustness of the SMC method. The PD control is utilized to stabilize the nominal model and the SMC is utilized to provide the robustness and to compensate the uncertainty and external disturbance of the controlled overhead crane systems. Moreover, to enhance the control performance of payload swing suppression and elimination, one additional term is introduced to the designed controller. Lyapunov techniques and Schur complement are utilized to analyze the asymptotically stable of the closed-loop system. Experimental results are illustrated to validate the effective and robustness of the new proposed control law.